Walking the Tightrope of Socialist Governance: A Strategic-Relational Analysis of Twenty-first-Century Socialism. (January 2019) - Nelson, Marcel
The process of socialist transformation in a democratic context presents many quandaries including walking a tightrope between pursuing substantive transformation that challenges existing social relations and remaining in power in view of political opposition stemming from such a challenge. The experiences of twenty-first-century socialism in Ecuador, Bolivia, and Venezuela provide different examples of ways of balancing the two imperatives. Nicos Poulantzas's writings on the state shed light on the importance of deepening democracy as part of any process of socialist transformation and on the limits of such a strategy. El proceso de transformación socialista en un contexto democrático presenta muchos dilemas que incluyen caminar en la cuerda floja entre perseguir una transformación sustantiva que desafía las relaciones sociales existentes y permanecer en el poder en vista de la oposición política que surge de tal desafío. Las experiencias del socialismo del siglo XXI en Ecuador, Bolivia y Venezuela proporcionan diferentes ejemplos de formas de equilibrar los dos imperativos. Los escritos de Nicos Poulantzas sobre el estado arrojan luz sobre la importancia de profundizar la democracia como parte de cualquier proceso de transformación socialista y los límites de dicha estrategia.